Pengembangan Aset Tanah Wakaf melalui Budidaya Ikan Lele Berbasis Bioflok di Desa Argodadi Kabupaten Bantul DIY - Siti Achiria; Unggul Priyadi (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to increase the ability to manage waqf land assets so that the community has additional income from biofloc-based catfish farming. The method of implementing this service used training and mentoring. The target partner for this service was Brongkol Hamlet, Argodadi Village, Bantul Regency, DIY. The instrument for evaluating community service activities used a questionnaire and was analyzed descriptively. The service results showed that training in the development of waqf land assets through biofloc-based catfish cultivation proved to increase the ability of the community to obtain additional income. This community service activity concludes that waqf land assets can be managed productively, one of which is through catfish farming.